Re-visioning Lee Tzu Pheng’s Feminist Poetics - Ade, Wernmei Yong (SARE: Southeast Asian Review of English, 2017)
In her influential essay, "When We Dead Awaken: Writing as Re-vision," Adrienne Rich defines re-visioning as "the act of looking back, of seeing with fresh eyes, of entering an old text from a new critical direction," and insists that it is, for women. Appropriating Rich, Lee Tzu Pheng outlines her own strategy of re-vision in the poem. This radical critique is aimed at challenging androcentric practices of reading, and offers in its stead what Patrocinio P. Schweickart refers to as "reading strategies consonant with the concerns, experiences and formal devices that constitute [women’s ]texts" (620).